1998
DOI: 10.1145/279361.279364
|View full text |Cite
|
Sign up to set email alerts
|

Performance characterization of a Quad Pentium Pro SMP using OLTP workloads

Abstract: Commercial applications are an important, yet often overlooked, workload with significantly different characteristics from technical workloads. The potential impact of these differences is that computers optimized for technical workloads may not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 16 publications
3
52
0
1
Order By: Relevance
“…Other studies of database workloads indicate that OLTP (online transaction processing) workloads are characterized by a large memory footprint, combined with a small critical working set [447], and by the reduced benefit from microarchitectural optimizations [397]. In addition, index searching in OLTP workloads requires a different cache design [60].…”
Section: Database Systemsmentioning
confidence: 99%
“…Other studies of database workloads indicate that OLTP (online transaction processing) workloads are characterized by a large memory footprint, combined with a small critical working set [447], and by the reduced benefit from microarchitectural optimizations [397]. In addition, index searching in OLTP workloads requires a different cache design [60].…”
Section: Database Systemsmentioning
confidence: 99%
“…-If a and b are placed far apart from one another and different threads perform both read and write accesses to their fields, then due to the cache coherency protocol (Keeton et al 1998) the different threads would invalidate the cache lines. Accessing a and then b will cause two cache misses and with it two BusRd/BusRdx events in higher probability.…”
Section: Experimenting With the Oi Refactoring Processmentioning
confidence: 99%
“…Therefore, re-evaluating the DBMS's performance is significant to both the computer architecture and database communities. Previous studies have shown that DBMS exhibits high cache miss rates and low CPU utilization [1]. Simultaneous Multithreading (SMT) [2] is a form of hardware multithreading, where a single physical multithreaded processor can execute multiple threads concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…In this implementation a thread is created for each client's transaction. 1 The intuition is to improve performance by utilizing the underlying thread mechanism provided by the operating system. This is further improved by using symmetric multi-processors (SMP) architectures.…”
Section: Introductionmentioning
confidence: 99%